Efektivitas Sistem Informasi Dan Komputerisasi Haji Terpadu (Siskohat) Dalam Meningkatkan Pelayanan Haji Di Kantor Kementerian Agama Kota Pekanbaru - Rafika Hilda Sulfa; Chandra , Pivit Septiary (Jurnal Administrasi Karya Dharma, 2023)
This research was conducted at the Office of the Ministry of Religion in Pekanbaru City.  The background of this research is the background of the author's involvement in conducting research on the effectiveness of SISKOHAT in improving Hajj services at the Office of the Ministry of Religion in Pekanbaru City.  It is difficult to collect data and lack of information for pilgrims and the registration of pilgrims is still done manually.  The purpose of this study was to determine the effectiveness of organizing the pilgrimage using the Integrated Hajj Information and Computerized System ( SISKOHAT ) at the Office of the Ministry of Religion in Pekanbaru City and what factors were hindering the implementation of the pilgrimage using the Integrated Hajj Information and Computerized System ( SISKOHAT ).  The analytical method used in this study is a qualitative method.  Data collection methods are carried out by means of observation, interviews and documentation.  There were 7 informants in this study.  Based on the results of research conducted by the author, it can be interpreted that the effectiveness of the Integrated Hajj Information and Computerized System (SISKOHAT) in improving Hajj services at the Office of the Ministry of Religion in Pekanbaru City has not been effective, this is due to several factors such as a lack of training for the development of Human Resources in  operate SISKOHAT, there is a shortage of organizers due to rolling HR, bandwidth is too small and device and network limitations impact time